THE ROLE OF RESEARCH COMPETENCIES AND RESEARCH PUBLICATION COMPETENCIES ON RESEARCH PERFORMANCE OF THE LECTURERS IN PRIVATE UNIVERSITIES IN BANDUNG” - Saptono Kusdanu Waskito (Dinasti International Journal of Education Management And Social Science, 2020)
The research performance of S1 Accounting Study Program lecturers in Metropolitan Bandung Raya reached 52.54% from 100%. There is a problem in the research performance of a lecturer. In Metropolitan Bandung Raya, Bandung is section of Metropolitan Bandung Raya. Its mean there is research performance of the lecturer in Bandung too.Blaskova (2014) explained, among others, that research competencies and research publication competencies are competencies that affect lecturers' research performance. This research is a quantitative method of research to find out how much lecturer research competence, publication competency of lecturers' research results and lecturer research performance, and how much influence lecturer research competence and research publication competence on lecturer research performance. Population 365.sample 191. This study proves Research competence and research publication competence of research results affect research performance partially and simultaneously because the value of t arithmetic is greater than the table and the value of F arithmetic> F table. Keywords: Research Competencies, Publication Competencies, Research Performance